2014
DOI: 10.1128/iai.01508-13
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Are a Source of Gamma Interferon during Acute Salmonella enterica Serovar Typhimurium Colitis

Abstract: Gamma interferon (IFN-␥) is an important driver of intestinal inflammation during colitis caused by Salmonella enterica serovar Typhimurium. Here we used the mouse colitis model to investigate the cellular sources of IFN-␥ in the cecal mucosa during the acute phase of an S. Typhimurium infection. While IFN-␥ staining was detected in T cells, NK cells, and inflammatory monocytes at 2 days after infection, the majority of IFN-␥-positive cells in the cecal mucosa were neutrophils. Furthermore, neutrophil depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…It has previously been shown by [14] that in CD4 + T cell-deficient mice, IFN-gamma production was due to CD8 + T cells. It has been shown that neutrophils are a source of IFN-γ during acute Salmonella colitis [15]. Our results show that IFN-γ mRNA and secretion of IFN-γ protein are differentially expressed after exposure to SEA.…”
Section: Conclusion/outlooksupporting
confidence: 53%
“…It has previously been shown by [14] that in CD4 + T cell-deficient mice, IFN-gamma production was due to CD8 + T cells. It has been shown that neutrophils are a source of IFN-γ during acute Salmonella colitis [15]. Our results show that IFN-γ mRNA and secretion of IFN-γ protein are differentially expressed after exposure to SEA.…”
Section: Conclusion/outlooksupporting
confidence: 53%
“…For example, classical Eomes-expressing NK cells produce IFN-γ and, in some settings, neutrophils, and inflammatory monocytes produce IFN-γ (Gordon et al, 2012; Kraaij et al, 2014; Spees et al, 2014). Further, T-bet-expressing ILC1s may express or induce additional effector mechanisms that act in conjunction with IFN-γ to elicit host defenses against C. difficile .…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-1β and IL-18 have been shown in vivo to be important for the survival of mice following oral salmonella infection, with IL-18 expression having a greater effect (45). The contributions of IL-1β and IL-18 to resistance are likely manifold; however, it has been shown that IL-18, in particular, is a critical driver of IFN-γ expression in T cells and possibly neutrophils during salmonella infection (46-48). The contributions of CXCL1, CXCL2, and CXCL5 to neutrophil chemotaxis have been extensively documented (49), as have the importance of neutrophil responses in controlling S T infection in the gut (12, 50, 51) where, neutrophil influx during salmonella infection is driven by production of CXC chemokines that are largely governed at the mucosal surface by the IL-17/IL-23 axis (52, 53).…”
Section: Discussionmentioning
confidence: 99%